Entrepreneurial marking: Beyond professionalism to creativity, leadership, and sustainability - Kotler, Philip; Kartajaya, Hermawan; Huan, Hooi den; Mussry, Jacky (Hoboken John Wiley & sons, Inc., 2023)
Marketing legend Phil Kotler and his colleagues explain why the conventional "professional" approach to marketing is no longer enough. Marketers must be more entrepreneurial, creative, and risk-taking, if they are to adapt to the challenges of the post-pandemic digital world. Entrepreneurial Marketing explains the basics of professional marketing and marketing operations, but also how this foundation must support entrepreneurial thinking and risk-taking.